PERANCANGAN BANGUNAN INTERNATIONAL SCHOOL MENGGUNAKAN MATERIAL BAMBU DENGAN PENDEKATAN ARSITEKTUR BERKELANJUTAN DI KOTA SEMARANG - Indira Setia Putri; Anityas Dian Susanti; Gatoet Wardianto (Jurnal Desain Lingkungan Binaan Indonesia, 2025)
To address the challenges of contemporary development, the phenomenon of global warming and other environmental degradation issues continues to grow. According to data collected by the World Green Building Council, 33% of carbon dioxide (CO2) emissions come from building construction. The goal of implementing development that complies with standards and improves the quality of life without harming future generations is driven by this influence. The coastal areas of Semarang City are vulnerable to extreme heat, especially in the downstream areas bordering the Java Sea. This phenomenon has given rise to the idea that to have a positive impact on the environment, economy, and society, sustainable buildings, especially those used for international school education, are essential. Regarding the concept of sustainability, specifically the idea of ​​extending the lifespan of natural resources, which relates to the potential lifespan of natural resources and the human ecological environment, including forestry, industry, agricultural systems, and architecture, the term "sustainable architecture" is commonly used in the field of architecture. The world is currently experiencing environmental degradation due to the overexploitation of natural resources. The most basic definition of sustainable architecture is environmentally friendly architecture.